PROMOTING STUDENTS’ CRITICAL THINKING THROUGH PEER FEEDBACK IN ORAL COMMUNICATION CLASSROOM - Faridah, Didih; Thoyyibah, Luthfiyatun; Kurnia, Asep Dudi (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2020)
Being able to speak critically requires think critically. This study explicates students? perception on the use of oral peer feedback/review in establishing their speaking ability and critical thinking. Peer feedback/review is commonly employed in the classroom learning process especially in writing and oral communication classroom. The study acquired a qualitative case study design. Questionnaires and interviews were disseminated to gain the data. The eighteen undergraduates? students of the English education program taking oral communication classroom entailed in this study. Findings indicated that most of the students perceived the beneficial use of oral peer feedback to enhance their oral communication speaking and critical thinking skills. They found that their peer feedbacks/review were very functional in establishing their oral communication skill. Defining the oral peer feedback/review, the students elucidated that it helped them in describing, analyzing, and evaluating critically what they had experienced. Concerning the findings, the students were able to reflect on their previous speaking performance and become more critical in analyzing and evaluating each of the performance sessions. Also, they were more aware of their comprehension of the materials taught in the classroom from the previous feedbacks/review. The findings profound that regular practices of oral peer feedback/review can be accomplished to develop students? critical thinking to speak critically. Future studies might explore the extent to which these peer feedback activities have a quantitative effect on students' critical thinking skills.